2016
DOI: 10.1123/jpah.2016-0398
|View full text |Cite
|
Sign up to set email alerts
|

Results From Brazil’s 2016 Report Card on Physical Activity for Children and Youth

Abstract: Background: Very few studies have comprehensively analyzed the physical activity of children and adolescents in Brazil. The purpose of this article is to show the methodology and summarize findings from the first Brazilian Report Card on Physical Activity for Children and Youth. Methods: Three Brazilian research institutions coordinated the activities to develop the Brazilian 2016 Report Card. The data available were collected independently and then synthesized by the Research Work Group using the grade system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…51 The low grades in most countries are consistent with earlier reports. 7,15,70 Grades were generally higher in low-middle income countries (LMIC; Brazil, 26 India, 37 Kenya, 40 Mexico, 42 Mozambique, 43 Nigeria, 46 South Africa, 52 Zimbabwe 61 ), but this relationship was not uniform as Slovenia 51 and New Zealand 45 also reported high grades and no significant correlation between HDI and overall behavior grades was observed (Table 5).…”
Section: Successes and Challenges Based On Indicator Gradesmentioning
confidence: 82%
“…51 The low grades in most countries are consistent with earlier reports. 7,15,70 Grades were generally higher in low-middle income countries (LMIC; Brazil, 26 India, 37 Kenya, 40 Mexico, 42 Mozambique, 43 Nigeria, 46 South Africa, 52 Zimbabwe 61 ), but this relationship was not uniform as Slovenia 51 and New Zealand 45 also reported high grades and no significant correlation between HDI and overall behavior grades was observed (Table 5).…”
Section: Successes and Challenges Based On Indicator Gradesmentioning
confidence: 82%
“…1 Nonetheless, data from Brazil's 2016 Report Card revealed that only 40% of children and youth (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) years old) met the recommendations for moderate-to-vigorous physical activity (MVPA). 2 This data also showed unfavorable grades for other behaviors (e.g., sedentary behavior and active transportation). This paper aims to summarize the results of Brazil's 2018 Report Card.…”
Section: Introductionmentioning
confidence: 80%
“…One fact that may explain the high risk of exposure of the Brazilian population to physical inactivity and, consequently, the high number of deaths due to ischemic heart disease in adulthood is the high number of children and adolescents in Brazil who do not meet recommendations for physical activity. A survey monitoring physical activity in Brazilian youth found that almost 60.0% of individuals did not meet physical activity recommendations 26 . Therefore, the findings of this study may suggest that the promotion of physical activity should begin with younger age groups, especially for the prevention of NCD.…”
Section: Discussionmentioning
confidence: 99%